Innovation and Adaptation of Social Studies Learning in Curriculum Development - Yulisan, Yulisan; Gunawan, Gunawan; Wuwun, Wuwun (JUPE : Jurnal Pendidikan Mandala, 2024)
In essence, social studies learning innovation is an effort to continuously improve the quality of the educational process, to meet the development of society's demands for education. In this way, innovation in social studies learning will be effective, if indicated by the results of evaluation and research in the field of social studies learning. Learning can be done in joint study groups, which emphasizes group learning. So far, it has been felt that it has not been deliberately developed in the learning process, therefore it is a challenge and demand for learning innovation. If done, it will be able to overcome the weaknesses of learning that has been carried out in the field. And the social studies teacher adaptation process is carried out by applying the Pancasila student profile in learning and attending several trainings to improve teacher abilities. The obstacles to this transition lie in human resources, teacher ability, lack of access to learning, as well as differences in students' understanding, thoughts and ways of thinking in understanding the Merdeka Belajar curriculum. Developments in the 21st century influence the development of the world of education, education has a very important role and responsibility to be able to overcome and answer problems that arise.